Variations in the use of discourse markers by L1 and L2 English users - Dumlao, Remart Padua; Wilang, Jeffrey Dawala (Indonesian Journal of Applied Linguistics, 2019)
This study adopts a functional approach to investigate specific discourse markers employed by L1 English and L2 English users in non-native English speaking contexts. Twenty-four academic essays were voluntarily submitted by the students for analysis. Primarily, Fraser’s (2009) taxonomy was used to identify discourse markers and to know its use in writing academic essays. Findings indicate that there were notable differences between L1 and L2 users in using discourse markers, specifically in its frequency and functions. Accordingly, L1 English users’ writings frequently displayed elaborative markers followed by temporal, inferential, and contransitive discourses. Meanwhile, L2 English users’ writings showed the overuse of certain discourse types such as temporal and inferential markers. In the coding of data, it was also revealed the L2 users’ overused of discourse markers resulted in incoherent texts. Language teachers may need to raise awareness of how discourse markers can be used variably in writing academic essays.